The Influence of Fashion Competence and The Implementation of TEFA-Based Learning (Teaching Factory) On The Work Readiness of Fashion Students Program - Choiria, Rini; Maspiyah, Maspiyah; Anifah, Lilik; Buditjahjanto, I Gusti Putu Asto (PT. EQUATOR SINAR AKADEMIA, 2025)
Vocational education has a strategic role in producing graduates who are ready to work, especially through expertise programs at Vocational High Schools (SMK). One area of expertise that is in demand is Fashion Management, which requires mastery of technical and non-technical competencies in order to compete in the competitive fashion industry. However, data shows that the open unemployment rate of SMK graduates, including those majoring in Fashion Management, is still quite high. This indicates a gap between the competencies of graduates and the needs of the world of work. To bridge the gap, the Teaching Factory (TEFA) learning model is applied to provide industry-based contextual learning experiences. This study aims to analyze the effect of Fashion Cosmetology competence and the implementation of TEFA learning on student work readiness, both partially and simultaneously, at SMKN 1 Turen. The results of previous empirical studies show that student competence and TEFA implementation contribute positively to strengthening work readiness, which includes cognitive, psychomotor, and affective aspects. By using a quantitative approach, this study is expected to prove that both variables have a significant effect on students' work readiness, and become the basis for developing a more effective, relevant, and industry-oriented vocational learning strategy.